Synchronization of Chaotic Quantum Dot Light Emitting Diodes under Optical Feedback Effect - Huda M. Ali,; Hussein B. Al Husseini, (University of Thi-Qar Journal of Science, 2020)
Chaos synchronization of delayed quantum dot light emitting diode has been studied theortetically which are coupled via the unidirectional and bidirectional. at synchronization of chaotic, The dynamics is identical with delayed optical feedback for those coupling methods. Depending on the coupling parameters and delay time the system exhibits complete synchronization, . Under proper conditions, the receiver quantum dot light emitting diode can be satisfactorily synchronized with the transmitter quantum dot light emitting diode due to the optical feedback effect.